Personality : The Essentials of Life - Kumar, Gajendra (Journal of Commerce and Trade, 2008)
It is a mirror of life and an image/name/position in the world. It is basis of all achievement, happiness & success. The present paper is a study of lecturers’ popularity & unpopularity on the basis of personality traits.Personality is the combination of external as well as internal qualities. Personality makes a place in the world. Personality provides the basis of people classification. Personality provides a recognition and image in the world. Success lies in personality. Personality includes – Attitude, Perception and Ways of living. The more attractive, pleasing and healthy personality, the more happiness, success and satisfaction.